Neoichnology of Rhinella dorbignyi (Bufonidae) burrows: improving the recognition and interpretation of toad burrows - Nascimento, Diego Luciano [UNESP]; Netto, Renata Guimarães; Cenci, Romulo; Villegas-Martín, Jorge (Taylor & Francis, 2024)
A neoichnological characterization of toad burrows from organic-rich soils is presented in order to establish key ichnological signatures for their recognition in the geological record. Dorbigny’s Toad (Rhinella dorbignyi) produces J-shaped burrows with a single elliptical opening resembling the ichnogenus Macanopsis. The burrow varies from 15 to 20 cm in length and has a constant diameter along the shaft, enlarged in the chamber. The shaft is elliptical with a diameter of 2.5-3.0 cm in the major axis and 1.0–1.5 cm in the minor axis. The chamber is semicircular, with a distinct floor, and an average diameter of 5 cm in the major axis. A thick (3–5 mm), compacted, smooth, and uniform inorganic lining made of soil covers the burrow throughout its length. Surficial features, such as horizontal and vertical millimeter-scale striations and ridges, occur in the burrow surface and are produced by keratinized granules and spikes on the skin of R. dorbignyi. Those surficial features are generated during the toad’s movements inside the burrow as well as anchoring during ambush predation behavior. The main distinct features observed on the burrow surface are well-developed circular pit impressions produced by the keratinized tubercles present in the toad’s ankles during climbing activity. These characteristics encompass useful ichnotaxobases for recognition and distinguishing toad burrows from J-shaped, Macanopsis-like burrows produced by other soil-dwelling animals. The burrow architecture of R. dorbignyi suggests that J-shaped burrows are efficient structures for ambush predatory behavior in terrestrial ecosystems, as observed in spiders and scorpions.
Keywords: amphibian; ichnology; Macanopsis; neoichnology; Rhinella dorbignyi